Uteroplacental Insufficiency Alters the Retinoid Pathway and Lung Development in Newborn Rats - Liang-Ti Huang; Hsiu-Chu Chou; Chun-Mao Lin; Chung-Ming Chen (Elsevier, 2016)
Intrauterine growth retardation (IUGR) is associated with reduced lung function during infancy and perhaps throughout adulthood. The retinoic acid (RA) signaling pathway modulates pre- and postnatal lung development. This study was conducted to test our hypothesis that uteroplacental insufficiency alters the elements of the retinoid pathway in developing lungs. Methods: On Gestation Day 18, either uteroplacental insufficiency was induced through bilateral uterine vessel ligation (IUGR group) or sham surgery (control group) was performed. Lung tissues from the offspring were examined through Western blotting, immunohistochemistry, and morphometry on Postnatal Day 3 and Postnatal Day 7. Results: Compared with control rats, the IUGR rats exhibited significantly lower body weights on Postnatal Day 3 and Postnatal Day 7 and significantly lower lung weights on Postnatal Day 3. Uteroplacental insufficiency significantly increased RA receptor (RAR)-β protein expression on Postnatal Day 3. The expression of RAR-α, RAR-γ, cellular RA-binding protein-1, and cellular RA-binding protein-2 between the control and IUGR rats was comparable on Postnatal Day 3 and Postnatal Day 7. Compared with the control rats, the IUGR rats exhibited a significantly higher volume fraction of alveolar airspace on Postnatal Day 3 and Postnatal Day 7 and a significantly lower volume fraction of alveolar walls on Postnatal Day 3. Conclusion: Uteroplacental insufficiency causes defective alveolarization and transient increases in RAR-β expression in the lungs of newborn rats. The retinoid pathway may be one of the probable pathways mediating lung abnormalities caused by uteroplacental insufficiency.